2018
DOI: 10.1136/bmjopen-2017-015875
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent drug use among methadone maintenance patients in mountainous areas in northern Vietnam

Abstract: ObjectivesWith the rise in methadone maintenance therapy (MMT) for drug users in Vietnam, there has been growing interest in understanding if and how often MMT patients engage in concurrent illicit drug use while on methadone therapy in various settings. This study examined factors associated with concurrent opioid use among patients on MMT in a mountainous area in Vietnam.SettingOne urban and one rural MMT clinics in Tuyen Quang province.ParticipantsSurvey participants consisted of patients who were taking MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…Our finding indicates that tobacco is the most common (81%) substance used among patients participating in the MMT program. This result is in line with previous reports which also found an extremely high level of cigarette use (the prevalence varies between 77% and 88%) in MMT patients [29,31]. Among middle-income countries, Vietnam has a high level of cigarette consumption [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding indicates that tobacco is the most common (81%) substance used among patients participating in the MMT program. This result is in line with previous reports which also found an extremely high level of cigarette use (the prevalence varies between 77% and 88%) in MMT patients [29,31]. Among middle-income countries, Vietnam has a high level of cigarette consumption [27].…”
Section: Discussionsupporting
confidence: 92%
“…Many factors believed to be involved in the concurrent use of opioids in MMT patients have been elucidated. Age of onset of opioid abuse [26], frequency of opioid use [27], peer pressure [27,28], living with family members who use heroin [29], and concomitant antiretroviral and tuberculosis treatment [27] have all been found to be positive predictors of concurrent opioid use in MMT patients.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we also found that the adherence among MMT clients was lower in the group having a history of drug injection or still used a drug when being treated with methadone. A higher level of psychological distress [47] and/or the contact with peer drug users, [18], which are considered an unproductive factor. The similarity between peers regarding drug use has been found in several studies [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…In the cultural context of Vietnam, it is typical that injecting drug users gather in a small group and share needles [ 11 , 12 ]. Drug injection has not only driven the expansion of the HIV epidemic in the community [ 13 ], but also increased catastrophic health expenditures [ 14 ]. Scaling up the MMT program would be a cost-effective solution to reduce HIV transmission [ 15 ].…”
Section: Discussionmentioning
confidence: 99%